Analysis of Regional Financial Independence and Effectiveness in North Buton District - Said Saleh Salihi (International Journal of Advanced Technology and Social Sciences, 2023)
This research aims to determine and analyze the regional financial independence and effectiveness of North Buton Regency. This research was quantitative. The technique of data collection in this research used secondary data by collecting a summary report on changes to the North Buton Regency Government's Regional Revenue and Expenditure Budget (APBD). The data analysis technique used a descriptive approach. The research results showed that the North Buton Regency Government was aware that it was still dependent on receiving transfer funds from the central government such as the General Allocation Fund and Special Allocation Fund so that it was hoped that it could maximize the potential for local revenue from the regional tax and levy sector to finance regional expenditure, especially capital expenditure, as evidenced by effectiveness analysis results based on APBD data from 2016 to 2020